What's mine is yours: the joint interest exception to legal professional privilege in Lambie Trustee Limited v Addleman. Issue 9 (3rd November 2021) - Barber, Simon
Abstract: In Lambie Trustee Limited v Addleman, New Zealand's Supreme Court sided with international authority in finding that trustees generally cannot assert legal professional privilege against beneficiaries to resist disclosure. The Court held that trustees and beneficiaries share a joint interest in trustees' legal advice because courts will assume such advice is for the benefit of beneficiaries. Joint interest will cease when this is no longer true. Most often, this will occur when a beneficiary files proceedings against a trustee. The difficulty, however, will be telling when correspondence alchemizes into an adverse claim before any proceedings are filed.